THYROID DYSFUNCTION IN PATIENTS WITH TYPE 1 DIABETES: A cross-sectional study - Khan, Gohar; Ghaffar, Tahir; Ahmed, Ibrar; Ullah, Faheem; Khan, Rabnawaz; Aamir, Aziz Ul Hassan (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the frequency of thyroid dysfunction in patients with type 1 diabetes mellitus using thyroid function tests. Methodology: This was a descriptive study conducted from January 2017 to June 2017. All patients presenting with type 1 diabetes mellitus (DM) were included irrespective of their age and gender. Thyroid status was determined by screening patients with thyroid stimulating hormone (TSH), free T4 (FT4) and free T3 (FT3). Patients were categorised into five groups consisting of euthyroid, subclinical/overt hypothyroidism and subclinical/overt hyperthyroidism. Results: One hundred and four patients comprising of 38 (36.5%) males and 66 (63.5%) females had an overall mean age of 20.5 ±4.4 years, mean body mass index (BMI) 24.9 ±1.6 and mean duration of diabetes of 3.7 ±1.4 years. The mean HBA1c was 7.9 ±0.71% and mean TSH was 5.4 ±4.4 m IU/mL. Twelve (11.5%) patients were hypothyroid, 16 (15.4%) had subclinical hypothyroidism and 76 (73.1%) were euthyroid. No case of hyperthyroidism was seen. Conclusion: Thyroid dysfunction especially overt and subclinical hypothyroidism were commonly found in patients with type 1 diabetes mellitus.